BASICS PRINCIPLES OF TRADING (IN THE LIGHT OF SIRAT-E-TAYYABA) - Dr.Khurram Sheraz; Dr. Makhdoom Muhammad Roshan Siddiqui; Dr. Tanveer Huma Ansari; Dr.Khalida Siddique; Dr. Sabiha Abdul Quddus; Unsa Khan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Trade is actually the voluntary exchange of goods and services. The original form of trade was barter, in which goods and services were directly exchanged.Modern traders generally use "Money" as a medium of trade rather than barter, thus, purchases are distinguished from sales or profits. The invention of money has made trade simple and uncomplicated and has given it further development. Trade between two traders is called bilateral trade while trade between more than two traders is called multilateral trade. Trading is also called the process by which traders and financial markets earn or perform. Trade is one of the sources of halal sustenance, which Allah liked and the Messenger of Allah, Muhammad (Peace Be Upon Him), Every job has some rules and regulations. which is necessary for its survival. Islam has declared trade as an excellent profession. The author of the paper has highlighted in detail in this paper: "Basic Principles of Trade in the light of the , Sirat e Tayyaba ". Which has an important place in Islamic economics.